Graves disease is more prevalent than Hashimoto disease in children and adolescents with type 1 diabetes - Wang, Lu-Ting; Huang, Chi-Yu; Lin, Chao-Hsu; Cheng, Bi-Wen; Lo, Fu-Sung; Ting, Wei-Hsin; Lee, Yann-Jinn (Frontiers in Endocrinology, 2023)
Introduction Autoimmune thyroid disease (AITD) is the most common associated autoimmune disorder in type 1 diabetes (T1D). Early detection of AITD is crucial to optimize glycemic control, growth, and intellectual development. In this prospective cohort study, we sought to characterize the prevalence, incident ages and risk factors of AITD in children and adolescents with T1D. Materials and Methods Patients with T1D diagnosed at ≤ 18 years at MacKay Children’s Hospital, Taipei, from 1990 to 2019 underwent annual screening for AITD. Institutional Review Board-approved data on age, sex, and disease profile are collected. Statistical analysis was performed by using independent sample t test for continuous variables, chi-squared test for categorical variables, and Kaplan-Meier estimates of cumulative incidence of AITD were calculated. A p value of <0.05 was considered statistically significant. Results We prospectively followed up 808 patients with T1D, 761 patients were included in the study. Of these patients, 197 (25.9%) of them had thyroid autoimmunity, meaning positivity of thyroid autoantibodies. Females had a higher prevalence of thyroid autoimmunity than males (59.9%, p = 0.012). Altogether, 5.5% patients developed AITD (4.4% had Graves disease; 1.4% had Hashimoto disease), at a mean age of 17.8 ±8.5 years. The cumulative incidence of AITD at 30 years of disease duration was 0.29 in the total group and was significantly higher in females (0.39, n = 397) than in males (0.15, n = 364, p<0.001). Discussion In Taiwan, the prevalence of AITD in pediatric population with T1D increases with age, a longer disease duration and female sex. For early detection of autoimmune thyroid disease in Taiwanese children and adolescents with T1D, an annual AITD screening program should be implemented.